THE ANALYSIS OF HUMAN ERROR AS CAUSES IN THE MAINTENANCE OF MACHINES: A CASE STUDY IN MINING COMPANIES - Kovacevic, Srdja; Papic, Ljubisa; Janackovic, Goran; Savic, Suzana (The South African Journal of Industrial Engineering, 2016)
This paper describes the two-step method used to analyse the factors and aspects influencing human error during the maintenance of mining machines. The first step is the cause-effect analysis, supported by brainstorming, where five factors and 21 aspects are identified. During the second step, the group fuzzy analytic hierarchy process is used to rank the identified factors and aspects. A case study is done on mining companies in Serbia. The key aspects are ranked according to an analysis that included experts who assess risks in mining companies (a maintenance engineer, a technologist, an ergonomist, a psychologist, and an organisational scientist). Failure to follow technical maintenance instructions, poor organisation of the training process, inadequate diagnostic equipment, and a lack of understanding of the work process are identified as the most important causes of human error.